Behavioral adaptation of sympatric rodents to early germination of oak acorns: radicle pruning and embryo excision - Zhang, Mingming; Yang, Xifu; Dong, Zhong; Liu, Shuyuan; Chen, Huanhuan; Yi, Xianfeng (Frontiers in Plant Science, 2023)
The seed germination schedule is a key factor affecting the food-hoarding behavior of animals and the seedling regeneration of plants. However, little is known about the behavioral adaptation of rodents to the rapid germination of acorns. In this study, we provided Quercus variabilis acorns to several rodent species to investigate how food-hoarding animals respond to seed germination. We found that only Apodemus peninsulae adopted embryo excision behavior to counteract seed germination, which is the first report of embryo excision in nonsquirrel rodents. We speculated that this species may be at an early stage of the evolutionary response to seed perishability in rodents, given the low rate of embryo excision in this species. On the contrary, all rodent species preferred to prune the radicles of germinating acorns before caching, suggesting that radicle pruning is a stable and more general foraging behavior strategy for food-hoarding rodents. Furthermore, scatter-hoarding rodents preferred to scatter-hoard and prune more germinating acorns, whereas they consumed more nongerminating acorns. Acorns with embryos excised rather than radicles pruned were much less likely to germinate than intact acorns, suggesting a behavioral adaptation strategy by rodents to the rapid germination of recalcitrant seeds. This study provides insight into the impact of early seed germination on plant–animal interactions.